Restoring the blessings of the morning star: childbirth and maternal-infant health for First Nations near Edmonton, Alberta - Wiebe, Adrienne D.; Barton, Sylvia; Auger, Laura; Pijl, Em M.; Foster-Boucher, Caroline (University of Alberta, 2015)
Open access article. It is not only remote Aboriginal communities in Canada that have poorer maternalinfant health status than Canadian averages; residents of First Nation communities located close to large urban centres also experience this health status gap. Alexander, Alexis, Enoch, and Paul First Nations are located within an hour of healthcare services in greater Edmonton. The narratives of 75 predominantly Cree and Stoney women from these communities were gathered through seven talking circles and five semi-structured interviews. The participants described their experiences of loss and separation as pregnancy care and childbirth moved out of the community and into the hospital over the last two generations. This shift was not only a geographic relocation; it also disconnected the childbirth experience from elders, family and community, traditional teachings, and spiritual meaning. Conversely, the participants’ hospital experiences were characterized by a limited sense of cultural safety. Participants highlighted the urgent need to reintegrate culturally based community support and health perspectives into the childbirth experience. The implementation of such a culturally integrated healthcare model in all Aboriginal communities—remote, rural, suburban, and urban—may be the key finally to closing the gap between Aboriginal and non-Aboriginal maternal and infant health status in Canada. Yes